Clinical significance of HER2 in urothelial carcinoma and analysis of its correlation with glycolytic metabolic characteristics - Guo, Andong; Wu, Chenrui; Cao, Jishuang; Zhu, Kejia; Ding, Sentai (Frontiers in Molecular Biosciences, 2024)
ObjectiveThis study aimed to explore the clinical relevance of Human Epidermal Growth Factor Receptor 2 (HER2) in urothelial carcinoma (UC) and its association with glycolytic metabolic markers, insulin resistance, and beta-cell function, shedding light on potential therapies targeting both HER2 pathways and cancer metabolism.MethodsIn this retrospective analysis, 237 UC patients from the Departments of Urology and Pathology at Shandong Provincial Hospital were examined. From 1 January 2023, to 1 October 2024, patients underwent HER2 testing using immunohistochemistry (IHC). We investigated the relationships between HER2 expression and metabolic indicators such as the Homeostatic Model Assessment for insulin resistance (HOMA-IR), beta-cell function (HOMA-β), the triglyceride-glucose (TyG) index, and lactate dehydrogenase (LDH) levels. HER2 status was determined using a standardized scoring system from the 2021 Clinical Pathological Expert Consensus on HER2 Testing in UC, China. Statistical analysis followed CDC guidelines, using multivariate logistic regression to assess the independent impacts of HER2 on metabolic traits.ResultsOf the 237 evaluated UC samples, 87.76% exhibited positive HER2 expression. A significant correlation was found between positive HER2 status, advanced tumor stages, and increased LDH levels, suggesting a link between HER2 expression and heightened glycolytic activity. No significant relationships were observed between HER2 status and TyG levels, HOMA-IR, or HOMA-B. Subgroup analyses confirmed the consistency of the relationship between HER2 expression and LDH levels across different demographics and lifestyle factors.ConclusionOur findings confirm the significant role of HER2 as a prognostic marker and therapeutic target in UC. The association of HER2 positivity with advanced tumor stages and high LDH levels underscores its complex involvement in disease progression. This study highlights the need to explore HER2’s biological mechanisms further and pursue combined therapeutic strategies.